2022
DOI: 10.1159/000525541
|View full text |Cite
|
Sign up to set email alerts
|

NELL1-Positive HIV-Associated Lupus-Like Membranous Nephropathy with Spontaneous Remission

Abstract: <b><i>Introduction:</i></b> Kidney biopsy findings in patients with human immunodeficiency virus (HIV) are diverse, and optimal therapy for the various immune complex diseases in the setting of HIV is unknown. <b><i>Case Presentation:</i></b> A man with well-controlled HIV developed nephrotic range proteinuria, and kidney biopsy revealed lupus-like glomerulonephritis with a predominantly membranous pattern of injury. He opted for conservative therapy and experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…An interesting study reported a possible association between mercury and NELL-1-associated MN [4]. NELL-1-associated MN has also been reported in patients with HIV infection [5].…”
Section: Discussionmentioning
confidence: 92%
“…An interesting study reported a possible association between mercury and NELL-1-associated MN [4]. NELL-1-associated MN has also been reported in patients with HIV infection [5].…”
Section: Discussionmentioning
confidence: 92%
“…A third patient had an initial biopsy with PLA2R+ NELL1-MN (no serum available), treated conservatively, with relapse >10 years later and biopsy demonstrating dual PLA2R+ NELL1+ MN with corresponding serum antibodies to both PLA2R and NELL1 (37). In two cases, PLA2R glomerular staining is described as weak with an incomplete capillary loop distribution and was associated with a negative serum anti-PLA2R antibodies at the time of biopsy (35,45,49), which may represent false-positive tissue reactivity.…”
Section: Dual Pla2r and Nell1 Positive Mnmentioning
confidence: 99%
“…Of reported patients, 9 of 12 (75%) with oncologic remission also had remission of proteinuria ( 13 , 42 ), supporting this link. Other conditions include infections – such as human immune deficiency virus (HIV) ( 35 ), hepatitis B and C (HBV, HCV) ( 40 ), tuberculosis ( 43 ). MN in the setting of hematopoietic stem cell transplant and graft-versus-host disease (GVHD) can occur with the NELL1 antigen ( 29 ) although is much more commonly associated with the protocadherin FAT1 antigen ( 18 ).…”
Section: Clinicopathologic Studies Of Nell1 Mnmentioning
confidence: 99%
“… 1 , 2 , 3 In 2019, 2 groups identified the NELL1 podocyte antigen in a subset of MN with distinct histologic and immunologic features, namely segmental or incomplete glomerular capillary loop involvement with predominant IgG1 staining. 4 , 5 NELL1 MN has also been identified in association with thiol-containing medications, namely lipoic acid, 6 , 7 bucillamine, 8 and tiopronin 9 ; traditional indigenous medications, including those with high mercury content 10 ; and with underlying conditions, including malignancy, 5 infections (including HIV 11 ), sarcoidosis, 12 hematopoietic stem cell transplant and graft-versus-host disease, 13 and rheumatoid arthritis. 8 …”
mentioning
confidence: 99%